Project TIBOK Talaan at Iba't Ibang Opinyon Para sa Komprehensibong Sitwasyonal na Analisis - Araza, John Kloyd P.; Dela Cruz, Ron Louis D.C; Guantia, Mary Gale R.; Martin, Ella Sheridy T.; Mateo, Eve Kathleen Marie E.; Medes, Jeandre Evan P.; Perfecto, Angeline M.; Pitallano, Jr., Noel M.; Punongbayan, Bea Mae V.; Ramoy, Maria Regina V.
Magallanes is a 4th class municipality that aims to serve as a focal point for agri-eco-tourism within the whole province of Cavite. It currently has 16 barangays under its jurisdiction, with a total population of 24, 528 as of 2023. There are 11 barangay health stations (BHS) and one Rural Health Unit (RHU) that are supervised by the Officer-in-Charge-Municipal Health Officer (OIC-MHO). In terms of the health system, a variety of health programs are being implemented in the Municipality of Magallanes, including the maternal and child care program, dental care program, and leprosy and rabies prevention and control program, among many others.